Pd (II) Complexes with Schiff Bases: Synthesis, Spectral Characterization, and X-Ray Diffraction Studies - Julekha A. Shaikh (Progress in Chemical Science Research Vol. 8, 2023)
Study Aim: To synthesize, characterize and investigate X-Ray Diffraction data of certain Pd (II) complexes containing bidentate Schiff bases. Herein, the synthesis, spectroscopic characterization and X-Ray Diffraction investigations of certain Pd (II) complexes containing bidentate Schiff bases were carried out. Various Schiff bases were synthesized by combining amines such as 4-nitro aniline, 4-methyl aniline and 4-methoxy aniline with aldehydes such as 2-hydroxy-1-naphthaldehyde and 5-chloro salicyladehyde. Further, the synthesized Schiff bases were complexed with Pd (II) salt and characterized using elemental analysis, FTIR, 1H-NMR and UV spectroscopy. Thermal analyses as well as molar conductivity were also carried out. X-ray diffraction studies revealed that these complexes possess a monoclinic crystal system. Moreover, all the synthesized Pd (II) complexes exhibit square planar geometry with 1:2 (metal: ligand) stoichiometry.